Praktik Bagi Hasil Usaha Ternak Sapi Perspektif Hukum Ekonomi Syari’ah (Di Desa Cigedug Kecamatan Cigedug Kabupaten Garut) - Syaripudin, Enceng Iip; Salwiyah, Salwa Siti (STAI Al Musaddadiyah Garut, 2023)
Profit sharing is a collaborative effort between capital owners and managers with the aim of obtaining their respective benefits, the practice of profit sharing carried out by the people of Cigedug Village, Cigedug District, there are two systems, namely fattening and breeding. The profit-sharing system carried out by the people of Cigedug Village depends on the agreement of both parties. This study aims to determine the practical mechanism for sharing the results of cattle farming in Cigedug Village. Thus, researchers hope that this research can be useful to be used as a reference for future researchers. The research method used is field research which covers the entirety of what happens in the field to explore and examine data related to research. The approach carried out by this research uses qualitative research. Based on the conclusions of the results of this study, the practice of sharing the results of cattle farming in Cigedug Village using a mudharabah contract is carried out orally, the distribution of results depends on mutual agreement. In addition, the view of shari'ah economic law on the practice of profit sharing of cattle in Cigedug Village is not entirely contrary to Islamic law and teachings but must be reviewed because there is still a gap about the mudharabah contract and its implementation is still ineffective. Keywords : Profit Sharing, Cattle Business, Sharia Economic Law